Strategy of the Jambi Provincial Health Service in Accelerating the Implementation of the Dumisake Program through the Jambi Sehat Card - Simanjorang, Yuniara; Rahmawati, Wulandari (Sustainability (STPP) Theory, Practice and Policy, 2023)
Strategy is steps containing indicative programs to realize the vision and mission, which are formulated with criteria including a rational relationship between the vision and mission with the program priorities of the elected regional head, a strong relationship with regional analysis and strategic issues, a general statement to guide development of an annual development program for five years, and developed in a regional strategy mapping. A strategy is needed to clarify the direction of development of regional heads' priority programs. The strategy created in essence does not stand alone but is related to the national development strategy and regional development strategy. The Jambi Provincial Health Service Strategy as a guideline in planning health development programs for the next 5 (five) years. The "Two Billion One District" or Dumisake program, which is one of the flagship programs of the Jambi Provincial Government, is an action and strategy of the regional government in alleviating poverty. The aim of this research is to evaluate the extent to which the dumisake program is running and implemented in accordance with applicable regulations, this will help the community to get the best service.